Implementasi Ekstrakurikuler Cabang Olahraga Futsal Putri Pada Sekolah Menengah Atas Di Kota Bengkulu - Bunga Surya Ningrum; yarmani yarmani; sofino sofino (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2020)
This study aims to determine the application in Bengkulu City High School with 5 items, namely: 1. Management, 2. Interests and participation, 3. Facilities and infrastructure, 4. Implementation, 5. Funding for female Futsal Extracurricular at Senior High Schools in Bengkulu City. The method used in this research is descriptive qualitative method. With research objects totaling 50 students with 5 high schools each, 11 SMA Negeri 1 Bengkulu City, 10 SMA Negeri 3 Bengkulu City, 12 SMA Negeri 4 Bengkulu City, 8 SMA Negeri 6 Bengkulu City and Muhammadiyah 4 High Schools Bengkulu City 9 Students. Based on data obtained from 5 schools that have female futsal extracurricular it can be concluded that the extracurricular implementation of female futsal sports in high schools in Bengkulu City is stated in good category with an average yield of 70.18%.